The Neutrality Dilemma of Civil Servant in 2020 Local Leaders Election on Malaka Regency - Hieronimus Vincentius Seran; David B. W. Pandie; Laurensius P. Sayrani (Dynamics of Politics and Democracy, 2022)
Purpose: This study discusses the problem of neutrality of civil servants in the government of Malaka Regency. There are indications of violations committed by civil servants during the campaign period. Research methodology: This research is a case study where the researcher investigates the phenomena that exist in the field. Results: (1) The dilemma of neutrality of civil servants in the 2020 Malaka Regional Election occurred because civil servants did not have the power or capacity to fulfill all aspects that would make them neutral, namely legal, material, strategic or superior aspects such as aspects of political action. (2) The cause of the neutrality dilemma for civil servants is due to the patron-client factor and position compensation. Limitations: Researchers find it difficult to meet civil servants in the Malaka district. Contribution: Propose efforts to prevent the dilemma of neutrality of civil servants in the 2020 Malaka Regional Head Election by implementing a merit system, clear division of tasks and free from political interference, rational hierarchical authority structure, impersonal relations between members, mechanism for appointment or recruitment and promotion of employee positions civil service based on technical skills and bureaucratic reform.